2016
DOI: 10.1088/0953-8984/28/8/086001
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic properties in low-doped zigzag graphene nanoribbons

Abstract: The temperature-dependent edge magnetic susceptibility [Formula: see text] and the uniform magnetic susceptibility χ in zigzag graphene nanoribbons is studied within the Hubbard model on a honeycomb lattice. By using the determinant quantum Monte Carlo (DQMC) method, it is found that the ferromagnetic fluctuations at the zigzag edge dominate around half-filling, and that the fluctuations are strengthened markedly by the on-site Coulomb interaction U, which may lead to a possible high-temperature edge ferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…[22][23][24][25][26][27][28] At graphene edges the density of states may be peaked due to the presence of edge-localized states close to the Fermi level. 29 Especially at extended zigzag edges this leads to a phenomenon called edge magnetism, for which various theories [30][31][32] predict ferromagnetic (FM) intraedge and antiferromagnetic (AFM) interedge correlations. The proposed magnetism is similar to the flat-band ferromagnetism appearing in the orbital-active optical honeycomb lattice, 33 where the band flatness dramatically amplifies the interaction effect, driving the ferromagnetic transition even with a relatively weak repulsive interaction.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] At graphene edges the density of states may be peaked due to the presence of edge-localized states close to the Fermi level. 29 Especially at extended zigzag edges this leads to a phenomenon called edge magnetism, for which various theories [30][31][32] predict ferromagnetic (FM) intraedge and antiferromagnetic (AFM) interedge correlations. The proposed magnetism is similar to the flat-band ferromagnetism appearing in the orbital-active optical honeycomb lattice, 33 where the band flatness dramatically amplifies the interaction effect, driving the ferromagnetic transition even with a relatively weak repulsive interaction.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 First-principles studies of graphene triangles (S = 0) and hexagons (S = 0) 4 further confirmed the applicability of Lieb's theorem concerning S in the half-filled one-orbital Hubbard model for bipartite lattices. 16 Upon charge doping, it was found in the same model that the spin polarizations on the two ribbon edges can change from antiparallel to parallel, forming the ferromagnetic correlated edge (FMCE)…”
mentioning
confidence: 81%
“…In fact, many of the recently discovered flat bands systems show an enhanced susceptibility towards superconductivity [27,31]. However, alternative orders have also been shown to be strongly enhanced, including flat band ferromagnetism [35,36] and robust magnetic order along the zigzag edge of graphene [37][38][39][40][41][42]. Thus, while ordering is very often expected in flat band systems, it is not generally known if the large DOS peak actually favors superconductivity or other orders.…”
Section: Introductionmentioning
confidence: 99%